152 The role of adamts-5 in extracellular matrix remodelling of thoracic aortic aneurysms. (5th June 2017) - Fava, Marika; Barallobre-Barreiro, Javier; Baig, Ferheen; Mayr, Ursula; Lynch, Marc; Joshi, Abhishek; Catibog, Norman; Gomes, Renata; Barwari, Temo; Youssefi, Pouya; Viviano, Alessandro; Yin, Xiaoke; et al.
Abstract : ADAMTS, aneurysm, ECM Introduction: Thoracic aortic aneurysms (TAA) are common in patients with bicuspid aortic valve (BAV). ADAMTS-1 (a disintegrin and metalloproteinase with thrombospondin motifs) has recently been implicated in TAA formation ( Oller et al, Nat Med, 2017). The contribution of other ADAMTS proteases to TAA is currently unknown. Method: Using proteomics, we compared the extracellular matrix (ECM) composition in the greater (i.e. the aneurysm-prone area) and lesser curvatures of TAA in BAV patients. Our findings in patients were complemented by studies in ADAMTS-5 deficient mice. Results: In BAV patients with TAA, the large aggregating proteoglycan versican was the most differentially regulated ECM protein in the aneurysm-prone area. In mice, ADAMTS-5 is the main versican-degrading member of the ADAMTS family. Hence, a model of aortic dilatation by angiotensin II (AngII) infusion was adopted in mice lacking the catalytic domain of ADAMTS-5 (Adamts-5 cd ). AngII treatment raised blood pressure in wild-type (WT) mice; this response was attenuated and associated with increased dilation of the ascending aorta in Adamts-5 cd mice. Concomitantly, versican accumulation and reduced versican degradation products were observed in Adamts-5 cd aortas compared to WT controls. The presence of other ADAMTS members, including ADAMTS-1, was not sufficient to maintain versican processing and prevent aortic dilation in Adamts-5 cd mice. Conclusion: Our results support the emerging role of ADAMTS proteases in TAA. ADAMTS-5 rather than ADAMTS-1 is the key protease for versican regulation in murine aortas. Further studies are needed to define the ECM substrates of the different ADAMTS proteases and their contribution to TAA formation.